Post-mortem neuropathologic examination of a 6-case series of CAR T-cell treated patients - Vidal Robau, Núria; Caballero, Gabriela; Archilla, Ivan; Ladino, Andrea; Fernández, Sara; Ortiz-Maldonado, Valentín; Rovira, Montserrat; Gómez-Hernando, Marta; Delgado, Julio; Suárez-Lledó, María; Fernández de Larrea, Carlos; Balagué, Olga; et al. (Free Neuropathology, 2022)
Introduction: Chimeric antigen receptor (CAR) T-cell therapy is a promising immunotherapy for the treatment of refractory hematopoietic malignancies. Adverse events are common, and neurotoxicity is one of the most important. However, the physiopathology is unknown and neuropathologic information is scarce. Materials and methods: Post-mortem examination of 6 brains from patients that underwent CAR T-cell therapy from 2017 to 2022. In all cases, polymerase chain reaction (PCR) in paraffin blocks for the detection of CAR T cells was performed. Results: Two patients died of hematologic progression, while the others died of cytokine release syndrome, lung infection, encephalomyelitis, and acute liver failure. Two out of 6 presented neurological symptoms, one with extracranial malignancy progression and the other with encephalomyelitis. The neuropathology of the latter showed severe perivascular and interstitial lymphocytic infiltration, predominantly CD8+, together with a diffuse interstitial histiocytic infiltration, affecting mainly the spinal cord, midbrain, and hippocampus, and a diffuse gliosis of basal ganglia, hippocampus, and brainstem. Microbiological studies were negative for neurotropic viruses, and PCR failed to detect CAR T -cells. Another case without detectable neurological signs showed cortical and subcortical gliosis due to acute hypoxic-ischemic damage. The remaining 4 cases only showed a mild patchy gliosis and microglial activation, and CAR T cells were detected by PCR only in one of them. Conclusions: In this series of patients that died after CAR T-cell therapy, we predominantly found non-specific or minimal neuropathological changes. CAR T-cell related toxicity may not be the only cause of neurological symptoms, and the autopsy could detect additional pathological findings.